Area-based management tools to protect unique hydrothermal vents from harmful effects from deep-sea mining: A review of ongoing developments - Blanchard, Catherine; Gollner, Sabine (Frontiers in Political Science, 2022)
The deep seabed in areas beyond national jurisdiction, or what is referred to as “the Area,” is the common heritage of humankind, safeguarded by mandating the International Seabed Authority (ISA) to protect the marine environment and to regulate all mining-related activities on the seabed in areas beyond national jurisdiction. So far, the ISA has 7 contracts for polymetallic sulfide (PMS) exploration. PMS deposits are located at and near deep-sea hydrothermal vents, one of the most remarkable ecosystems on Earth. Where hot and mineral rich vent fluids escape from the earth's crusts, minerals precipitate and are deposited, and unique biomass rich microbial and animal communities are thriving. Several intergovernmental organizations suggest that active vents classify as areas in need of conservation. The ISA is currently developing regional environmental plans for PMS and has set some first steps to protect active vents from mining impacts. We review the current regulatory and policy framework for deep-sea spatial management, and set it into the environmental context. We conclude that all current management measures of the ISA would not be suited to protect the marine environment from harmful mining impact. We recognize that ISA's area-based management tools are under development, and suggest that improvements can be achieved by studying and recognizing the ecological attributes of ecosystems and their connectivity, as well as governance connectivity, taking into account area-based management tools of different users in the same area.